Non-clinical toxicity testing for vaccines - Plitnick, Lisa (Henry Stewart Talks, 2009)
Preclinical development, Testing required prior to and in some cases concurrent with the administration of novel developmental candidates to volunteers and/or patients in clinical trials, Vaccines, Biologic entity designed to elicit a protective immune response, May be prophylactic or therapeutic
Archived at 2022/02/02